THE ASSESSMENT OF PATIENTS' PERCEPTION AND SATISFACTION OF RADIOLOGY WAITING TIME IN UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL - Nwobi IC; Luntsi G; Ahmadu MS; Nkubli FB; Kawu HD; Dauda F; Moi AS; Abubakar GM; Tahir MB (Ntec Specialist, 2014)
The patient is the most important person in the entire hospital setup and it is the duty of the health care personnel to give special attention to the management of patient to enhance effective service delivery. Waiting time is the total time from registration until consultation with healthcare personnel. It is an aspect of care that patients value most. Objective: The aim of this study was to evaluate Patients' perceived satisfaction with waiting time in Department of Radiology, University of Maiduguri Teaching Hospital, Borno State Nigeria. Method: The study was a cross-sectional prospective survey, that targeted patients who presented at the radiology department for HSG and IVU over the period of six months with a response rate of 70%, (n=70). The mean age of the participants was 33.6years. Data was collected using a 23 item self-completion questionnaire designed in line with the objectives of the study. Data were categorized into groups and analyzed using statistical package for social sciences version 16.0, where descriptive statistics such as the mean, percentages and frequencies were generated and tabulated. Pearson's correlation at p less than 0.01(2 tailed) was used to test for relationship Results: The results showed that 64.3%, (n=45) were female while 35.7%, (n=25) were male, out of these, 42.9% (n=30) were referred for HSG, and 57.1% (n=40) were for IVU. Among the patients referred for IVU, 37.5%, (n=15) were female, and 62.5%, (n=25) were male. Waiting time (before and after investigation) and satisfaction was found to be significant at (p less than 0.01, 2-tailed), with the waiting time. Conclusion: Insufficient number of counter service staff (Receptionist) and insufficient number of Radiologist and Radiographers were some of the factors that affect patient's satisfaction with waiting time, as investigations and reports were delayed